2021
DOI: 10.1111/jdv.17663
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between topical corticosteroid phobia and susceptibility to misinformation in patients with atopic dermatitis

Abstract: Physical examination revealed a maculopapular erythematous rash on his trunk and extremities (Fig. 1g,h). PBC revealed eosinophilia (1650/µL; 21.0% of WBC 7860/µL). Histopathological examination showed vacuolar dermatitis with spongiotic changes. (Fig. 1i). After discontinuation of apalutamide and administration of daily oral prednisolone (10 mg, 0.15 mg/kg), the skin lesions improved rapidly, and prednisolone was tapered and discontinued within a week.In addition to the three cases presented here, five other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…27 Furthermore, higher levels of TCP were recorded in subjects considered at a high risk of being misinformed, as determined by the results of a specifically structured questionnaire, namely, the bullshit receptivity score system. 28 In this regard, it should not be overlooked that the mean age of the study patients was relatively high. Online health-seeking behavior and access to online based resources, which seems to fuel corticophobia, 24,27 tend to be less frequent among older subjects.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…27 Furthermore, higher levels of TCP were recorded in subjects considered at a high risk of being misinformed, as determined by the results of a specifically structured questionnaire, namely, the bullshit receptivity score system. 28 In this regard, it should not be overlooked that the mean age of the study patients was relatively high. Online health-seeking behavior and access to online based resources, which seems to fuel corticophobia, 24,27 tend to be less frequent among older subjects.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, previous studies showed that the main sources of misinformation on TCs, in terms of exaggerated risks, are friends/family and the Internet 27 . Furthermore, higher levels of TCP were recorded in subjects considered at a high risk of being misinformed, as determined by the results of a specifically structured questionnaire, namely, the bullshit receptivity score system 28 . In this regard, it should not be overlooked that the mean age of the study patients was relatively high.…”
Section: Discussionmentioning
confidence: 93%
“…This can lead AD patients and their caregivers opting for nonconventional treatment options, to find quick fixes for their cutaneous issues that have great visual and psychosocial impact. Especially at risk of experiencing corticophobia are those who are more susceptible to pseudo-profound information, namely information that is encoded in profound sounding statements, which actually make very little sense [13]. Indeed, AD has a complex multifactorial aetiology, which is at higher risk of formulation of false myths and diffusion of misinformation, as many different systems are involved in the true disease aetiology, including skin-barrier dysfunction, T helper 2 cell-skewed immunity, and dysbiosis [11].…”
Section: Introductionmentioning
confidence: 99%